Electrochemical and electrocatalytic properties of self-assembled single-walled carbon nanotube/organo-iron hybrid systems on gold electrodes - Ozoemena, Kenneth I. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.